The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1039/c9ta01089k
|View full text |Cite
|
Sign up to set email alerts
|

Reviving bulky MoS2 as an advanced anode for lithium-ion batteries

Abstract: The high intrinsic Li storage capacity of bulky MoS2 is readily released by a rationally designed composite with a 3D conductive carbon skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…[13][14][15][16][17] Unfortunately,c onsiderable capacity fading caused by its intrinsic low electronic conductivity,a ggregation,a nd pulverization on extended cyclingcannotbeavoided by mere nanostructure engineering. Thus,a nother strategy of integrating nanostructured MoS 2 with highly conductive materials, such as graphene, [18][19][20] amorphous carbon, [21,22] carbon nanotubes (CNT), [23,24] and conductingp olymers, [25][26][27][28] has been proposed to solve the abovementioned problems. Besides the advantages of nanostructured MoS 2 ,t he mechanicallys table and electronically conductive carbon component serving as ac onductive skeleton in the hybrid configuration can effectively enhancet he conductivity of the electrode, buffer the volume change,a nd thus resulti n improved cycling performance and rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Unfortunately,c onsiderable capacity fading caused by its intrinsic low electronic conductivity,a ggregation,a nd pulverization on extended cyclingcannotbeavoided by mere nanostructure engineering. Thus,a nother strategy of integrating nanostructured MoS 2 with highly conductive materials, such as graphene, [18][19][20] amorphous carbon, [21,22] carbon nanotubes (CNT), [23,24] and conductingp olymers, [25][26][27][28] has been proposed to solve the abovementioned problems. Besides the advantages of nanostructured MoS 2 ,t he mechanicallys table and electronically conductive carbon component serving as ac onductive skeleton in the hybrid configuration can effectively enhancet he conductivity of the electrode, buffer the volume change,a nd thus resulti n improved cycling performance and rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…[34] The hierarchical structure could greatly increase the specific surface area of the electrode materials, which is contact with the electrolyte to accelerate the diffusion of Na + .O ur group fabricated ah ierarchical three-dimensional (3D) MoS 2 @C/RGO structure via as urfacem odification-induced self-assembly process (Figure 7b). [33] Bulky MoS 2 coated with a polydopamine (PDA) layer possessed ah ydroxylated surface and hence it could be uniformly distributed in 3D porous RGO framework duringt he hydrothermals ynthesis. The abundant N atoms in PDA-derived carbons erved as ab ridge to contact bulky MoS 2 with the RGO matrix.…”
Section: Cases To Applicationmentioning
confidence: 99%
“…b) Schematic illustration of the synthesis strategyo f 3D MoS 2 @C/RGO composite (reproduced with permission, [33] Copyright Royal SocietyofC hemistry,2019). Polysulfide outflow investigation of separators in differentL icycles c, d) withouta nd e, f) with PDA coating layer( reproduced with permission, [33] Copyright Royal SocietyofC hemistry,2019). g) Cycling performanceo fa s-prepared3 DM oS 2 @C/RGO composite at 200 mA g À1 (reproduced with permission, [33] CopyrightR oyal Society of Chemistry,2 019).…”
Section: Charge Storage In Sibs and Kibsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal dichalcogenide MoS 2 is considered a new semiconducting material because of its unique features such as direct band gap, conductivity, and biocompatibility. Several studies have reported the application of MoS 2 for capacitors and batteries [ 52 , 53 , 54 , 55 ]. Here, a thiol-modified single-stranded DNA layer was anchored on the Au substrate.…”
Section: Electrical Charge Storage Devicementioning
confidence: 99%